PENGARUH PENGGUNAAN APLIKASI KEUANGAN DIGITAL DAN KREDIT USAHA RAKYAT TERHADAP PENDAPATAN UMKM DI KECAMATAN MEDAN SUNGGAL - Fahmi, Habib; Dewi, Sucitra; Ananda, Rana Fathinah (Bussman Journal : Indonesian Journal of Business and Management, 2025)
The purpose of this research is to determine the impact of using digital financial applications and people’s business credit on the income of MSME in the Medan Sunggal District. The sample in this study consisted of 44 respondents who are MSME actors in the Medan Sunggal District, using a saturated sample. The type of data in this study is quantitative data. The data collection method used in this study was through questionnaires. The data analysis techniques used in this study employ Validity Test and Reliability Test. Data were processed using the program (SPSS version 15). The results of this study indicate that the use of digital financial applications has a positive and significant impact on MSME income, People’s Business Credit has a positive and significant impact on MSME income, and simultaneously, the use of digital financial applications and People’s Business Credit has a positive and significant impact on MSME income in the Medan Sunggal District.